"I am so ashamed of my body": Obese guests' experiences in hotels. (January 2021) - Poria, Yaniv; Beal, Jeremy; Shani, Amir
Highlights: The hotel experiences of obese guests have been ignored. Examining the experiences of obese guests in hotels is of ethical and practical importance. The experience of obese guests is compromised by physical and social impediments. Obesity should be conceptualized as a social disability. The difficulties obese guests face and suggestions for overcoming them are detailed. Abstract: The hotel experience of obese people is examined in this exploratory study, addressing a segment of the population thus far ignored by hospitality scholars. The findings are based on 32 semi-structured interviews with American obese men and women living in the Virginia area. The results revealed that almost all participants' hotel experience was affected by constraints arising from the physical environment, but more so, from other guests gazing at them. The thematic analysis of the experiences of obese hotel guests suggest that two relevant spaces in the hotel can be distinguished: the guest room and the public space accessible to all guests. These spaces differ in the difficulties experienced as well as the emotions that evoked among those guests. Overall, the findings indicate that people's body and its image is crucial for the understanding of the hotel experience, as lookism is a critical barrier obese people face.